Editorial - Warren Bareiss (Qualitative Research in Medicine & Healthcare)
As we put the finishing touches on Volume 5, Issue 3 of QRMH, I have much to be thankful for as Editor. First, I will be the first to say that I couldn’t put this journal together without Teresa Carrara, Managing Editor at PAGEPress Journals. Teresa fields initial correspondence with authors, does a lot of the editing, solves problems as they occur with the website, and works with Claudia Castellano on page layout and proofs. Most important, Teresa keeps on my case and doesn’t let me slide on anything. She has a knack for reminding of tasks that need to be done and for saving me from making mistakes. She is also determined to keep QRMH on track and on time. Oh, and she tells me when my perfectionist tendency goes too far. I can’t imagine how I would do my job without Teresa’s formidable contributions in the editorial and production process. [...]